Films applied to the surface of optical equipment, optical equipment, paint

JP7651294B2Active Publication Date: 2025-03-26CANON KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020208220
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-16
Publication Date
2025-03-26
Estimated Expiration
2040-12-16

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、長期間にわたって低酸素状態で太陽光に曝されても変色が少なく、遮熱効果が高い膜を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651294000007
    Figure 0007651294000007
  • Figure 0007651294000008
    Figure 0007651294000008
  • Figure 0007651294000009
    Figure 0007651294000009
Patent Text Reader

Abstract

To provide a film that has high thermal barrier performance and resists discoloration against sunlight in a hypoxic state.SOLUTION: A film includes porous particles having pores with an average pore diameter of 2 nm or more and 100 nm or less, titanium oxide particles having silica coating, and a resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film for suppressing a temperature rise due to sunlight, a paint for forming the film, and an optical device having the film formed thereon. [Background technology]

[0002] Since the performance of optical devices is easily affected by temperature rise, a technique is known in which a heat-shielding film is provided on the surface of the lens barrel, the main body of the optical device, or the housing that covers the optical device to suppress temperature rise of the components due to sunlight. For example, as shown in Figure 5, a heat-shielding film 4 with high infrared reflectance is provided on the light incident side of a base material 5, and the ratio of reflected light 2 to incident light 1 is increased, thereby suppressing temperature rise due to transmitted light 3.

[0003] Since the energy distribution of sunlight is 47% in the visible light region and 50% in the infrared region, high reflectance from the visible light region to the infrared region is required for the heat shielding film 4. General-purpose titanium oxide particles, which exhibit high reflectance for light with wavelengths of 400 to 1200 nm, are suitable as a material for forming the heat shielding film 4.

[0004] In addition, when a heat-shielding film is installed on equipment that is often used outdoors, the heat-shielding film must also be light-resistant. Labels with identification information or tapes for design purposes are often attached to the surface of the light-shielding film by users, and then peeled off. For this reason, light resistance is also required when the tape makes it difficult for oxygen to be supplied from the outside (low-oxygen conditions).

[0005] Patent Document 1 discloses a heat shielding film that contains titanium oxide particles coated with silica and silica nanoparticles that are smaller in particle size than the titanium oxide particles, thereby suppressing discoloration due to exposure to sunlight in a low-oxygen environment. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-180236 A Summary of the Invention [Problem to be solved by the invention]

[0007] Although the film of Patent Document 1 has excellent light resistance and heat shielding properties, discoloration occurs when exposed to sunlight in a low-oxygen environment for a long period of time.

[0008] The present invention has been made in view of the above background art, and provides a film which shows little discoloration even when exposed to sunlight in a low-oxygen environment for a long period of time and has high heat-shielding properties. [Means for solving the problem]

[0009] The membrane according to the present invention , many The porous particles, the titanium oxide particles having a silica coating, and the resin are included. The porous particles are at least one selected from the group consisting of silica, silica gel, diatomaceous earth, zeolite, ferrite, aluminum oxide, cellulose, and acrylic, have pores with an average pore size of 2 nm to 100 nm, and have an average particle size of 0.5 μm to 14 μm. It is characterized by:

[0010] The article according to the present invention has a surface that receives light from the outside. , many A membrane including porous particles, titanium oxide particles having a silica coating, and a resin is provided. The porous particles are at least one selected from the group consisting of silica, silica gel, diatomaceous earth, zeolite, ferrite, aluminum oxide, cellulose, and acrylic, have pores with an average pore size of 2 nm or more and 100 nm or less, and have an average particle size of 0.5 μm or more and 14 μm or less. It is characterized by the following.

[0011] Furthermore, the paint according to the present invention , many The porous particles, the titanium oxide particles having a silica coating, and the resin are included. the porous particles are at least one selected from the group consisting of silica, silica gel, diatomaceous earth, zeolite, ferrite, aluminum oxide, cellulose, and acrylic, have pores with an average pore size of 2 nm or more and 100 nm or less, and have an average particle size of 0.5 μm or more and 14 μm or less; It is characterized by: Effect of the Invention

[0012] According to the present invention, it is possible to provide a film which shows little discoloration even when exposed to sunlight in a low-oxygen environment for a long period of time and has a high heat-shielding effect. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic cross-sectional view of a membrane according to the present invention covered with tape. [Diagram 2] FIG. 1 is a schematic view of the appearance of an optical device as one embodiment of an article provided with a film according to the present invention. [Diagram 3] FIG. 2 is a schematic diagram showing a measurement form of reflectance using a spectrophotometer. [Figure 4] FIG. 13 is a schematic diagram showing a method for evaluating temperature. [Diagram 5] 1A and 1B are diagrams illustrating a technology for suppressing a temperature rise of a component due to sunlight. [Figure 6] FIG. 2 is a schematic cross-sectional view showing a state in which a film containing titanium oxide particles is exposed to sunlight. [Figure 7] 1 is a schematic cross-sectional view showing a state in which a film containing titanium oxide particles and silica nanoparticles having a silica coating is covered with tape and irradiated with sunlight. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Preferred embodiments of the present invention will now be described.

[0015] [Method for achieving both the prevention of discoloration caused by sunlight and the heat shielding effect under low-oxygen conditions] ]

[0016] (Discoloration of titanium oxide due to sunlight and methods for preventing it) As shown in FIG. 6, when sunlight 6 is irradiated onto a heat shielding film containing titanium oxide particles 11 and resin 9 in an air atmosphere, electrons in the valence band of titanium oxide are excited, and electrons (e - )7 and holes (h + When the silica coating 12 is not present on the surface of the titanium oxide particle 11, the cation M + 10 is attracted to the excited electron 7 and bonds with Ti, forming TiO 2 As in Patent Document 1, when a silica coating 12 is provided on the surface of a titanium oxide particle 11, even if an electron 7 is generated by excitation with sunlight 6, the silica coating 12 acts as a barrier to prevent the cation M +This can suppress the bonding between 10 and Ti. Furthermore, the excited electrons 7 and holes 8 are subsequently recombined, so discoloration of titanium oxide can be suppressed.

[0017] However, the silica coating 12 has micro defects. Therefore, when this heat insulating coating is exposed to a harsh environment with a lot of ultraviolet light for a long time, the cation M + 10 is attracted to the excited electrons 7 and gradually penetrates into the titanium oxide particles 11 through minute defects in the silica coating 12, and the titanium oxide is reduced. However, if no tape is attached to the surface of the heat shielding film and oxygen is supplied from the outside, the oxygen supplied from the outside will combine with TiO to form TiO 2 Therefore, coloring is suppressed.

[0018] (Discoloration of titanium oxide due to sunlight with tape attached) When a thermal barrier film containing titanium oxide particles having a silica coating 12 with a tape attached to the surface is exposed to a harsh environment with a lot of ultraviolet light for a long period of time, cations M+ gradually penetrate into the titanium oxide particles through minute defects in the silica coating 12, reducing the titanium oxide. Then, because the tape attached to the surface results in a state in which little or no oxygen is supplied from the outside, there is a shortage of oxygen to bond with TiO, and the titanium oxide changes color from white to a bluish color.

[0019] In the case of a film including a resin 9, titanium oxide particles 11 having a silica coating 12, and silica nanoparticles 17, as in the film according to Reference 1 (FIG. 7), the minute defects 16 in the silica coating 12 are blocked by the silica nanoparticles 17, and the cation M + However, since it is not possible to block all the micro defects 16, the intrusion of cations M + 10 penetrates into titanium oxide particles 11 and causes the reduction of titanium oxide. Therefore, when exposed to sunlight in a low-oxygen state for a long period of time, the titanium oxide particles discolor, resulting in discoloration of the film.

[0020] (Method of the present invention for suppressing discoloration even under hypoxic conditions) As described above, even if the surface of titanium oxide particles is covered with an inorganic film such as silica and silica nanoparticles are placed in the film, it is difficult to prevent the bonding between the cations contained in the resin and Ti.

[0021] The present inventors have thoroughly investigated methods for further suppressing discoloration under low-oxygen conditions and have found that adding the porous particles 20 of the present invention to the membrane 100, as shown in Figure 1, is highly effective in suppressing discoloration under low-oxygen conditions.

[0022] When the titanium oxide particles 10 are covered with tape 15 and exposed to sunlight 6 in a low-oxygen state, some of the oxygen defects 13 present in the titanium oxide particles 10 are reduced to TiO. However, oxygen contained in the voids in the porous particles is supplied, and the TiO is oxidized to TiO. 2 It is presumed that this will result in the color returning to the original color and inhibiting discoloration.

[0023] Furthermore, the heat shielding coating containing the porous particles 20 of the present invention has an increased effect of suppressing temperature rise. This is presumably because the porous particles 20 have high heat absorption and dissipation properties, so that moisture adsorbed in the pores of the porous particles is released by an increase in the surrounding temperature, and the heat of vaporization suppresses the temperature rise.

[0024] [Paint according to the present invention] The coating material for forming the film according to the present invention and the method for producing the coating material will now be described.

[0025] ≪Ingredients≫ The coating material includes porous particles, titanium dioxide particles having a silica coating, a resin, and a solvent.

[0026] (porous particles) The average pore size of the porous particles of the present invention is 2 nm or more and 100 nm or less, and more preferably 10 nm or more and 50 nm or less. If the average pore size of the porous particles of the present invention is less than 2 nm, discoloration of titanium oxide due to sunlight in an oxygen-free atmosphere will worsen. If the average pore size of the porous particles of the present invention exceeds 100 nm, the amount of moisture absorption will increase, and the adhesion of the film will decrease under high temperature and humidity conditions. The average pore size means the peak value of the pore volume in the pore size distribution measured by the gas adsorption method.

[0027] The average particle size of the porous particles of the present invention is preferably 0.5 μm or more and 14 μm or less, and more preferably 1 μm or more and 10 μm or less. If the average particle size of the porous particles of the present invention is less than 0.5 μm, the titanium oxide tends to discolor when exposed to sunlight in a low-oxygen state, and if the average particle size exceeds 14 μm, the adhesion of the film tends to decrease. Note that the average particle size means the particle size at 50% of the cumulative particle number count in the particle size distribution obtained by the laser diffraction / scattering method.

[0028] The amount of the porous particles added is preferably 0.5% by volume to 20% by volume, more preferably 1% by volume to 10% by volume, based on the nonvolatile content. If the amount of the porous particles added according to the present invention is less than 0.5% by volume, the titanium oxide tends to discolor when exposed to sunlight in a low-oxygen environment, whereas if the amount added exceeds 20% by volume, the amount of moisture absorption increases, and there is a risk of a decrease in adhesion between the substrate and the film in a high-temperature and high-humidity environment.

[0029] Any material can be used for the porous particles. Examples include organic materials such as silica, diatomaceous earth, zeolite, ferrite, aluminum oxide, cellulose, and acrylic. Porous particles made of one type of material selected from these groups, or a combination of multiple types of porous particles, can be used.

[0030] The shape of the porous particles can be any shape. Examples of the shape of the porous particles of the present invention include spherical, irregular, plate-like, needle-like, star-like, chain-like, and hollow. Particles of one type of shape selected from these may be used, or particles of multiple types of shapes may be used in combination.

[0031] (Titanium oxide particles with silica coating) As the titanium oxide particles, particles made of rutile type titanium oxide or anatase type titanium oxide can be used.

[0032] The titanium oxide particles are coated with a silica (silicon oxide) film. If the titanium oxide particles do not have a silica coating, the titanium oxide will discolor significantly in a low-oxygen atmosphere, resulting in a decrease in reflectance. The titanium oxide particles may be coated with a plurality of materials, such as zirconium oxide, aluminum oxide, and organic substances, in addition to silica. The amount of silica coating on the titanium oxide particles is preferably 0.5% by volume or more and 40% by volume or less, and more preferably 2% by volume or more and 15% by volume or less. If the amount of silica coating is less than 0.5% by volume, discoloration will tend to occur in a low-oxygen atmosphere, and if it exceeds 40% by volume, the solar reflectance may decrease.

[0033] The average particle size of the titanium oxide particles having a silica coating (hereinafter, sometimes simply referred to as titanium oxide particles) is preferably 0.2 μm or more and 5 μm or less. If the average particle size of the titanium oxide particles is less than 0.2 μm, the solar reflectance may decrease and the heat shielding properties may decrease, and if the average particle size exceeds 5 μm, the coating film may peel off.

[0034] The amount of titanium oxide particles having a silica coating contained in the paint is preferably 20% by mass or more and 60% by mass or less based on the non-volatile components in the paint. If the titanium oxide content is less than 20% by mass, the proportion of sunlight transmitted through the coating film increases, tending to deteriorate the reflectance, while if it exceeds 60% by mass, the film may become embrittled.

[0035] (resin) As the resin contained in the paint, any material can be used as long as it can ensure adhesion to the substrate on which the coating film is formed. Examples of resins include epoxy resin, urethane resin, acrylic resin, urethane acrylic resin, fluororesin, silicone resin, phenolic resin, and alkyd resin. One type of resin selected from these may be used, or multiple types of resins may be mixed and used.

[0036] The amount of resin contained in the coating material is preferably 20% by mass to 60% by mass, more preferably 30% by mass to 55% by mass, based on the non-volatile content. If the resin content is less than 20% by mass, adhesion to the substrate may deteriorate, and if it exceeds 60% by mass, the solar reflectance of sunlight may decrease.

[0037] (solvent) The solvent contained in the paint may be any material. Examples of the solvent include water, thinner, ethanol, isopropyl alcohol, n-butyl alcohol, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether, toluene, xylene, acetone, cellosolves, glycol ethers, and ethers. The paint may contain one or more of these solvents.

[0038] The viscosity of the paint is preferably from 10 mPa·s to 10,000 mPa·s, and more preferably from 50 mPa·s to 500 mPa·s. If the viscosity of the paint is less than 10 mPa·s, there is a risk that the thickness of the heat shielding film after application will be thin in some places, and if it exceeds 10,000 mPa·s, there is a risk that the applicability of the paint will decrease.

[0039] (Other additives) The coating composition of the present invention may contain other optional additives.

[0040] Other additives include those exemplified as the additives contained in the film.

[0041] Examples of such additives include pigments, dispersants, curing agents, curing catalysts, plasticizers, thixotropy-imparting agents, leveling agents, matting agents, preservatives, ultraviolet absorbers, antioxidants, coupling agents, inorganic and organic fine particles for adjusting color other than those mentioned above, and solid silica.

[0042] When a pigment is used, it is preferable that the paint film can be adjusted to have a brightness of 50 or more, and more preferably adjusted to have a brightness of 60 or more. If the pigment has a brightness of less than 50, the solar reflectance tends to decrease, and the effect of suppressing temperature rise tends to decrease. In addition, it is preferable that the pigment reflects or transmits infrared rays. As the pigment, an organic pigment or an inorganic pigment may be used, or a combination of these may be used.

[0043] Examples of organic pigments include azomethine black, perylene pigments, etc. Examples of inorganic pigments include Co-Zn-Si, Co-Al, Co-Al-Cr, Co-Al-Cr-Zn, Co-Al-Zn-Ti, Co-Ni-Zn-Ti, Ti-Cr-Sb, Ti-Fe-Zn, Fe-Zn, Fe-Cr, Mn-Bi, Co-Cr-Zn-Sb, Cu-Cr, Cu-Cr-Mn, Cu-Fe-Mn, Mn-Y, Mn-Sr, Co-Cr-Zn-Al-Ti, Co-Cr-Zn-Ti, Ti-Cr-Sb, P-Ba-Sr, etc.

[0044] The pigment may be of any color. For example, black, brown, yellow, red, blue, purple, pink, green, and orange may be used. One of these pigments may be selected for use, or a mixture of multiple pigments may be selected for use.

[0045] The amount of pigment contained in the paint is preferably 15% by mass or less. If the pigment content exceeds 15% by mass, the color of the coating film may become darker and the brightness may decrease. The pigment may be added as needed, and the content may be 0% by mass.

[0046] The paint may contain silica particles for the purpose of filling micro-defects present in the silica coating, as in the cited document 1. The silica particles preferably have an average particle size of 10 nm or more and 110 nm or less. If the average particle size of the silica particles is less than 10 nm, the effect of suppressing discoloration in a low-oxygen state tends to decrease. If the average particle size of the silica particles exceeds 110 nm, the force of attraction to the titanium oxide particles is weakened, and the effect of suppressing discoloration in a low-oxygen state may decrease. The silica particles may be particles of any shape, such as spherical, irregular, star-shaped, chain-like, hollow, or porous. Among these, particles of one type of shape may be used, or particles of multiple types of shapes may be included.

[0047] The amount of silica particles contained in the paint is preferably 0.5% by mass or more and 20% by mass or less, more preferably 1% by mass or more and 10% by mass or less. If the content of silica particles is less than 0.5% by mass, the minute defects 16 in the silica coating cannot be filled, and the effect of suppressing discoloration in a low-oxygen state tends to decrease. Also, if the content of silica particles exceeds 20% by mass, the haze of the coating film increases, and the reflectance may deteriorate.

[0048] ≪Manufacturing method≫ The method for producing the coating material according to the present invention can be any known method as long as it can disperse the titanium oxide particles having a silica coating and the porous particles in the coating material. For example, the components required for the coating material described above are weighed out and mixed and dispersed using a bead mill, ball mill, jet mill, three-roller, planetary rotating device, mixer, ultrasonic disperser, homogenizer, etc.

[0049] [Membrane according to the present invention] Next, the film according to the present invention will be described. Fig. 1 shows a schematic cross-sectional view of a film 100 according to the present invention covered with a tape 101. The film 100 according to the present invention contains titanium oxide particles 10 having a silica coating 11, porous particles 20, and a resin 14, and has a high solar reflectance and a heat shielding effect.

[0050] <Material composition> The film contains the porous particles, silica-coated titanium oxide, resin, and other components contained in the paint described above, so a duplicated explanation will be omitted. Note that the resin contained in the coating liquid in liquid form is contained in the film in a hardened state, and the solvent is volatilized when the paint is hardened, so it is hardly contained in the film.

[0051] The amount of the porous particles contained in the film according to the present invention is preferably 0.5% by volume or more and 20% by volume or less, and more preferably 1% by volume or more and 10% by volume or less. If the amount of the porous particles added according to the present invention is less than 0.5% by volume, the discoloration of titanium oxide due to sunlight in an oxygen-free atmosphere may worsen. If the amount of the porous particles added according to the present invention is more than 20% by volume, the amount of moisture absorption increases, and the adhesion of the film may decrease under high temperature and humidity conditions.

[0052] The amount of titanium oxide particles having a silica coating contained in the film according to the present invention is preferably 20% by mass or more and 60% by mass or less. If the content of titanium oxide particles having a silica coating is less than 20% by mass, sunlight may pass through the coating film, resulting in a decrease in reflectance. If the content of titanium oxide particles having a silica coating exceeds 60% by mass, the brittleness of the film may decrease.

[0053] The amount of the resin contained in the film according to the present invention is preferably 10% by volume or more and 80% by volume or less, more preferably 15% by volume or more and 70% by volume or less. If the content of the resin of the present invention is less than 10% by volume, the adhesion to the substrate may deteriorate. If the content of the resin of the present invention is more than 80% by volume, the solar reflectance of sunlight may decrease.

[0054] <Film thickness> The film of the present invention preferably has a thickness of 10 μm or more and 70 μm or less. If the film thickness is less than 10 μm, the solar reflectance may decrease. If the film thickness is more than 70 μm, peeling may occur.

[0055] <Method of forming film of the present invention> The film of the present invention can be formed by any coating method or curing method as long as the heat insulating coating material of the present invention can be uniformly applied to a thickness of 10 μm or more and 70 μm or less.

[0056] Examples of the method for applying the heat-shielding film for optical equipment of the present invention include brush application, spray application, dip coating, transfer, etc. The heat-shielding film may be applied in one layer or multiple layers, and may be textured to provide a design.

[0057] The heat shielding film for optical equipment of the present invention may be cured by leaving it at room temperature, promoting the curing with any heat, or applying ultraviolet rays. Examples of the method for curing by applying heat include a heating furnace, a heater, and infrared heating. The curing temperature is preferably in the range of room temperature to 400°C, more preferably in the range of room temperature to 200°C.

[0058] Characteristics of the membrane of the present invention ≫

[0059] (Solar reflectance) The film according to the present invention preferably has a solar reflectance of 50% or more and 98% or less. If the solar reflectance is less than 50%, the heat shielding effect may decrease. In addition, in order to increase the solar reflectance to more than 98%, it is necessary to include a large amount of titanium oxide in the film, which tends to increase the brittleness of the film.

[0060] (brightness) The film according to the present invention preferably has a brightness of at least 50. If the brightness is less than 50, the reflectance decreases, and there is a risk of the heat shielding effect decreasing.

[0061] [Article provided with the film according to the present invention] The film according to the present invention is provided on a surface that receives light from the outside of an article. Fig. 2 shows an external schematic diagram of an optical device as one embodiment of an article provided with a film according to the present invention, specifically, an interchangeable lens for a camera having a lens barrel. The interchangeable lens has a lens barrel 30 and a tripod mount 33. The lens barrel 30 is composed of a fixed barrel 31, an annular member 32, etc., and a lens optical system composed of a plurality of lenses (not shown) is installed inside. The film according to the present invention, which contains titanium oxide particles having a silica coating, porous particles, and a resin, is provided on the surfaces of the fixed barrel 31, annular member 32, and tripod mount 33 of the lens barrel 30 that receive light from the outside.

[0062] By providing the film according to the present invention on the surface of each component constituting an interchangeable lens, discoloration of the film and a decrease in reflectance can be suppressed even when the film is exposed to sunlight for a long period of time in a low-oxygen environment, and therefore an excellent heat-shielding effect can be exhibited, and the temperature rise of the interchangeable lens can be suppressed. Although an example of an interchangeable lens is shown in Fig. 7, the film can be provided on the surface of any article whose temperature rise due to exposure to sunlight should be suppressed, such as the main body of an imaging device or the housing of a security camera or weather camera that is permanently installed outdoors.

[0063] Any material can be used for the surface of the article (sometimes called the substrate) on which the film according to the present invention is provided, but metal or plastic is preferable. Examples of metal materials include aluminum, titanium, stainless steel, magnesium alloy, etc. Examples of plastic materials include polycarbonate resin, acryl resin, ABS resin, fluororesin, etc.

[0064] In addition, the thickness of the article can be set arbitrarily, but in the case of a member constituting an interchangeable lens, the thickness is preferably 0.5 mm to 5 mm, more preferably 0.5 mm to 2 mm. If the thickness is less than 0.5 mm, it is difficult to maintain the shape of the lens barrel. Also, if the thickness exceeds 5 mm, the cost becomes high.

[0065] (Primer layer) In order to improve the adhesion between the film according to the present invention and the article on which the film is to be provided, a primer layer may be provided on the surface of the article on which the film is to be provided.

[0066] Any material can be used for the primer layer, and examples include epoxy resin, urethane resin, acrylic resin, silicone resin, fluororesin, etc. The primer layer may also contain particles of the present invention or particles other than those of the present invention, a colorant, a dispersant, a curing agent, a curing catalyst, a plasticizer, a thixotropic agent, a leveling agent, an organic colorant, an inorganic colorant, a preservative, an ultraviolet absorbing agent, an antioxidant, a coupling agent, and solvent residues.

[0067] The thickness of the primer layer is preferably from 2 to 30 μm, more preferably from 5 to 20 μm. If the thickness is less than 2 μm, the adhesion of the film may decrease, and if it exceeds 30 μm, the film may peel off. EXAMPLES

[0068] Preferred embodiments of the present invention will now be described.

[0069] In Examples 1 to 11, preparation of the paint, production of the film, evaluation of discoloration in an oxygen-free atmosphere, evaluation of solar reflectance after a light resistance test in an oxygen-free atmosphere, evaluation of the temperature reduction effect after a light resistance test, and evaluation of adhesion after being left in a high-temperature, high-humidity atmosphere were performed by the methods described below.

[0070] <Evaluation of discoloration in an oxygen-free environment> A color difference meter (SE-7700; Nippon Denshoku) was used to evaluate discoloration in an oxygen-free atmosphere. * , a * , b * The film of the present invention was formed on a metal plate having a size of 30 mm square and a thickness of 1 mm and used as a sample for measurement. The metal plate was made of either stainless steel, aluminum, titanium, or a magnesium alloy. The film of the present invention was applied to a magnesium alloy metal plate with a spin coater to a thickness of 50 μm and then baked. After baking, the L value of the film of the present invention was measured using a color difference meter. * , a * , b* The value of was measured. Cellophane tape (CT-12M; Nichiban) was attached to the upper surface of the film of the present invention, and the film was subjected to a light resistance test for 400 hours in a light resistance tester (SUNTESTXXL+; ATLAS) under conditions of a radiation intensity of 50±2 W / m2 at 300 nm to 400 nm and a black panel temperature of 63°C±3°C. After the light resistance test, the cellophane tape was peeled off from the film and washed with acetone, and the L value of the film of the present invention was measured with a color difference meter within 24 hours. * , a * , b * The color change in an oxygen-free atmosphere (ΔE * ) was calculated using equation (1).

[0071] ΔE * =√((L before light resistance * - L after light fastness * )2+(a before light resistance * -A after light fastness * )2+(b before light fastness * - b after light fastness * )2)...Equation (1) Calculated ΔE * Based on the values, each film was evaluated on a four-level scale as follows.

[0072] A;ΔE * <0.6 B;0.6≦ΔE * <1.0 C;1.0≦ΔE * <1.5 D;1.5≦ΔE * ΔE * If ΔE is less than 0.6, it can be said to be a good film with very little color change. * If ΔE is 0.6 or more and less than 1.0, the film can be said to be good. * If ΔE is 1.0 or more and less than 1.5, the color change will be somewhat large, but it can be said to be within the acceptable range. * If the value is 1.5 or more, the color change is large and the film cannot be said to be good.

[0073] <Solar reflectance evaluation> The evaluation of solar reflectance after the light resistance test under low oxygen conditions will be described below. As shown in Figure 3, the solar reflectance was measured using a spectrophotometer (U-4000, Hitachi High-Tech) and then converted into solar reflectance.

[0074] First, the reflectance measurement method will be described. As shown in FIG. 3, incident light 1 with a wavelength of 300 nm to 2500 nm was incident on an integrating sphere 19. First, a blank of an alumina sintered body that causes 100% reflection was placed on a mounting part 20 for a test piece tilted by 5° with respect to the incident light 1, and a baseline measurement was performed. Next, a test piece on which the film of the present invention was formed was placed instead of the blank on the test piece mounting part 20, and light with a wavelength of 300 nm to 2500 nm was made to be incident, and the light was detected by a detector 21 to measure the reflectance. Next, the measured reflectance was multiplied by a weighting value (weighting coefficient) based on JIS-K560 (method of determining solar reflectance of a coating film) and integrated, and the solar reflectance was calculated from the integrated value.

[0075] The film of the present invention was formed on a metal plate having a thickness of 1 mm and a square of 30 mm for the measurement sample. The metal plate was made of stainless steel, aluminum, titanium, or magnesium alloy. The film of the present invention was applied to a magnesium alloy metal plate with a spin coater to a thickness of 50 μm and then baked. Cellophane tape (CT-12M; Nichiban) was attached to the upper surface of the film of the present invention, and the film was subjected to a light resistance tester (SUNTESTXXL+; ATLAS) for 200 hours under the conditions of a radiation intensity of 50±2 W / m2 at 300 nm to 400 nm and a temperature of the black panel of 63°C±3°C. After the light resistance test, the cellophane tape was peeled off from the film and washed with acetone, and the reflectance of the film was measured within 24 hours using a spectrophotometer at a wavelength of 300 mm to 2500 nm, and the solar reflectance was calculated based on JISK 560 and evaluated according to the following three stages.

[0076] A: Solar reflectance is 65% or more B: Solar reflectance is 50% or more and less than 65% C: Solar reflectance is less than 50% If the solar reflectance is 65% or more, the heat shielding effect is high and it can be said to be a very good film. If the solar reflectance is 50% or more but less than 65%, the heat shielding effect is relatively high and it can be said to be a good film. If the solar reflectance is less than 50%, the heat shielding effect is insufficient and it cannot be said to be a good film.

[0077] <Temperature reduction effect after light resistance test> Fig. 4 is a schematic diagram showing a method for evaluating temperature. A 120mm x 120mm x 120mm cardboard with a self-colored surface was used as the temperature measurement jig 25, and a 90mm x 90mm window was provided in the area where the test piece 23 for temperature evaluation was attached. A Hilux MT150FD6500K (Iwasaki Electric) was used as the lamp 22.

[0078] A film of the present invention was formed on a metal plate having a size of 100 mm square and a thickness of 1 mm and used as the test piece 23 for temperature evaluation. The metal plate was made of any of stainless steel, aluminum, titanium, and magnesium alloy, and the coating liquid of the present invention was applied to the metal plate with a spin coater to a thickness of 50 μm, and then baked to form a film.

[0079] The test piece 23 was attached to the temperature measuring jig 25 so that the light from the lamp 22 was incident from the formed film side, and a thermocouple 24 was attached to the surface of the test piece 23 opposite the film. The temperature measuring jig 25 to which the test piece 23 for temperature evaluation was attached was set so that the distance from the lamp 22 was 100 mm. Next, the lamp 22 was irradiated for 60 minutes, and the temperature after 60 minutes was measured.

[0080] To evaluate the heat-shielding effect of the film, a black blank was formed on the surface of a metal plate with the same 100 mm square and 1 mm thickness as the test piece 23 for temperature evaluation, and the temperature was measured in the same manner, and the difference ΔT from the temperature measurement result of the film of the example was calculated to determine the heat-shielding effect. The black blank was made by applying paint made by mixing 20 g of carbon black (MA100, Mitsubishi Chemical), 100 g of epoxy resin (jER828, Mitsubishi Chemical), 70 g of amine hardener (STll, Mitsubishi Chemical), and 20 g of thinner using a planetary rotation device to the surface of the test piece 23 and baking it.

[0081] The heat shielding effect was evaluated on a four-point scale based on the following criteria.

[0082] A: 12℃≦ΔT B: 10℃≦ΔT<12℃ C: 7℃≦ΔT<10℃ D: ΔT<7℃ If ΔT is 12°C or more, it can be said that the film has an extremely excellent heat-shielding effect. If ΔT is between 10°C and 12°C, it can be said that the film has a good heat-shielding effect, and if ΔT is between 7°C and 10°C, it can be said that the film has no problems. Also, if ΔT is less than 7°C, it cannot be said that the film has a sufficient heat-shielding effect.

[0083] <Adhesion evaluation after exposure to high temperature and humidity> The test piece for evaluating the adhesion after exposure to a high-temperature, high-humidity atmosphere was a metal plate with a 100 mm square and a thickness of 1 mm, on which the film of the present invention was formed. The metal plate was made of stainless steel, aluminum, titanium, or a magnesium alloy. The film of the present invention was applied to the metal plate with a spin coater to a thickness of 50 μm, and then baked.

[0084] Next, the prepared test pieces for adhesion evaluation were placed in a thermostatic oven at 65°C and 95% humidity for 100 hours. After 100 hours, the test pieces for adhesion evaluation were removed and subjected to a cross-cut test within 24 hours. The cross-cut test conforms to JISk5600-5-6, and 100 squares were cut at 1 mm intervals with a cutter, cellophane tape was applied and then peeled off to check for peeling of the coating, which was evaluated on the following three-point scale.

[0085] A: No significant peeling is observed. B: When the cutter cut area is enlarged, peeling occurs at the edge of the film. C: Peeling of one or more squares occurs If no peeling is observed, the film is considered to be in good condition. If peeling is observed only at the edge of the cutter's notch, the film is considered to be in relatively good condition. Also, if peeling is observed in one or more squares, the film is not considered to be in good condition.

[0086] [Example 1] <Paint preparation> The components listed below were weighed out and stirred for 10 minutes with a planetary rotating device (AR-100, Thinky) to prepare the coating material of Example 1.

[0087] Titanium oxide particles JR-701 (average particle size 0.26 μm, silica surface coating; Sakai Chemical Industry): 150 g (25% by volume of coating film) Resin (Olestar Q-691; Mitsui Chemicals): 100g (55.7% by volume of coating film) Porous particles (710 (pore diameter 2.5 nm); Fuji Silysia): 7 g (2% by volume of coating film) Pigment (Chromofine Black Al103; Dainichi Seika Chemicals): 1g (0.5% by volume of coating film) Hardener (Takenate D-120N; Mitsui Chemicals): 30g (16.7% by volume of coating film) Thinner: 100g <Membrane preparation> The above coating material was applied to a test piece for evaluating discoloration in an oxygen-free atmosphere, a test piece for evaluating solar reflectance, a test piece for evaluating heat shielding effect, and an evaluation of adhesion after exposure to a high temperature and high humidity atmosphere, so that the film thickness was 50 μm, and then dried at room temperature overnight. After that, the film was baked at 130° C. for 30 minutes to obtain the film of Example 1.

[0088] [Examples 2 to 11] In Examples 2 to 11, coating materials and films were prepared in the same manner as in Example 1, except for the materials and conditions shown in Tables 1 and 2.

[0089] The porous particles used in each example are as follows:

[0090] Examples 2, 4, 5, and 6: Silica 250 (Fuji Silica, Silica) Example 3: Large pore silica gel (Asahi Glass, silica gel) Example 7: MP powder (UD, diatomaceous earth) with an average pore size of 25 nm was ground in a planetary ball mill to an average particle size of 5 μm. Example 8: Porous particles 250 (Fuji Silicia) with an average particle size of 5 μm were placed in a planetary ball mill, stirred for 10 minutes, and classified with a sieve to adjust the average particle size to 0.5 μm. Example 9: Porous particles 250 (Fuji Silicia) with an average particle size of 5 μm were placed in a planetary rotary ball mill, stirred for 10 minutes, and classified with a sieve to adjust the average particle size to 1 μm. Example 10: Silica 470 (Fuji Silica) Example 11: Sunsphere H-201 (AGC Si-Tech) [Table 1] [Table 2]

[0091] (Evaluation Results) By the above method, the discoloration (ΔE * The results of evaluation of the film thickness (mm), solar reflectance (R), heat shielding effect, and adhesion after exposure to a constant temperature and high humidity environment according to the aforementioned criteria are shown in Tables 3 and 4. [Table 3] [Table 4]

[0092] [Comparative Examples 1 to 3] For comparison, films of Comparative Examples 1 to 3 were prepared using the components shown in Table 5 in the same manner as in the Examples, and the discoloration (ΔE * ), solar reflectance (R), temperature reduction effect, and adhesion after being left in a constant temperature and high humidity atmosphere were evaluated. Table 6 shows the evaluation results for the films of Comparative Examples 1 to 3. [Table 5] [Table 6]

[0093] As can be seen from Tables 1 to 6, the films of the examples containing titanium oxide particles having a silica coating and porous particles having an average pore size of 2 μm to 100 μm were all good in the evaluation results. In contrast, Comparative Example 1, in which the average pore size of the porous particles was 0.4 μm, and Comparative Example 3, which did not contain porous particles, were discolored when exposed to light in a low-oxygen state, and the heat-shielding effect was reduced. In Comparative Example 2, in which the average pore size of the porous particles was 300 μm, discoloration in a low-oxygen state was suppressed and the heat-shielding effect was good, but the adhesion after being left in a high-temperature, high-humidity atmosphere was not good. [Industrial Applicability]

[0094] The film formed on the upper surface of the optical device of the present invention can be used for the lens barrels of optical devices such as cameras, videos, and broadcasting equipment, as well as other camera bodies, video bodies, surveillance cameras, weather cameras, etc. that may be used outdoors. [Explanation of symbols]

[0095] 1 Incident light 2 Reflected light 3 Transmitted light 4. Infrared reflective film 5 Base material 6. Sunlight 9, 14 Resin 11 Titanium dioxide 12 Silica coating 13 Oxygen vacancies 15 Tape 16 Microdefects in Silica 20 porous particles 30 Lens barrel 31 Fixed tube 32 Annular member 33 Tripod mount

Claims

1. A method for producing a porous material comprising the steps of: porous particles; titanium oxide particles having a silica coating; and a resin; The porous particles include At least one selected from the group consisting of silica, silica gel, diatomaceous earth, zeolite, ferrite, aluminum oxide, cellulose, and acrylic; The porous membrane has an average pore diameter of 2 nm or more and 100 nm or less, The average particle size is 0.5 μm or more and 14 μm or less. A membrane characterized in that

2. 2. The membrane according to claim 1, wherein the content of the porous particles is 0.5% by volume or more and 20% by volume or less.

3. 3. The membrane according to claim 2, wherein the content of the porous particles is from 1% by volume to 10% by volume.

4. The membrane according to any one of claims 1 to 3, characterized in that the porous particles comprise one type of porous particles selected from the group consisting of silica, silica gel, and diatomaceous earth.

5. 5. The film according to claim 1, wherein the brightness is 50 or more.

6. a film containing porous particles, titanium oxide particles having a silica coating, and a resin is provided on a surface that receives light from the outside; The porous particles include At least one selected from the group consisting of silica, silica gel, diatomaceous earth, zeolite, ferrite, aluminum oxide, cellulose, and acrylic; The porous membrane has an average pore diameter of 2 nm or more and 100 nm or less, The average particle size is 0.5 μm or more and 14 μm or less. An article characterized by the above.

7. 7. The article according to claim 6, wherein the amount of the porous particles contained in the film is 0.5% by volume or more and 20% by volume or less.

8. 8. The article according to claim 7, wherein the content of the porous particles is 1% by volume or more and 10% by volume or less.

9. 9. The article according to claim 6, wherein the porous particles include porous particles made of any one type selected from the group consisting of silica, silica gel, and diatomaceous earth.

10. The article according to any one of claims 6 to 9, further comprising a primer layer between the surface of the article and the film.

11. the article is an interchangeable lens including a lens barrel having a fixed barrel and an annular member and equipped with a lens optical system composed of a plurality of lenses therein, and a tripod mount; 11. The article according to claim 6, wherein the film is provided on a surface of the fixed barrel and the annular member that receives light from the outside.

12. 12. The article according to claim 6, wherein the film has a thickness of 10 μm or more and 70 μm or less.

13. A method for producing a porous porous material comprising the steps of: a porous particle; a titanium oxide particle having a silica coating; and a resin; The porous particles include At least one selected from the group consisting of silica, silica gel, diatomaceous earth, zeolite, ferrite, aluminum oxide, cellulose, and acrylic; The porous membrane has an average pore diameter of 2 nm or more and 100 nm or less, The average particle size is 0.5 μm or more and 14 μm or less. A paint characterized by:

14. 14. The coating material according to claim 13, characterized in that the porous particles are contained in an amount of 0.5% by volume to 20% by volume based on the nonvolatile content.

15. 15. The coating material according to claim 14, wherein the porous particles are contained in an amount of 1% by volume to 10% by volume based on the nonvolatile content.

16. 16. The paint according to claim 13, wherein the porous particles are made of one type of porous particles selected from the group consisting of silica, silica gel, and diatomaceous earth.

Citation Information

Patent Citations

  • Curable coating material composition

    JP1998130584A

  • Optical semiconductor fine particle

    JP2008043848A

  • Lens barrel and imaging system

    JP2009139856A

  • Heat-blocking film, heat-blocking paint, and optical instrument

    JP2017194632A

  • Optical instrument, film on surface of optical instrument, and coating used in optical instrument

    JP2018180236A